1994
DOI: 10.4141/cjps94-138
|View full text |Cite
|
Sign up to set email alerts
|

Direct seeding of alfalfa in grain stubble and bromegrass sod

Abstract: Rioux, R. 1994. Direct seeding of alfalfa in grain stubble and bromegrass sod. Can. J. Plant . Direct seeding of alfatfa (Medicago sativaL.l is a valuable-alternative to conventional seeding. However, yield and nutritive value of forage obtained in the sefring year by direct seeding are not documented for Eastern Canadian conditions. The objective of this glul-V was to assess the foraie potenii"l ofulf"lf" direct seeded into a grain stubble and a bromegrass sod. In the grain stubble' alfalfa development was sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Weed biomass was concentrated in the first harvest and generally decreased in subsequent harvests (data not presented). Rioux (1994) also reported severe weed infestation when alfalfa sod‐seeding followed broadcast application of glyphosate at high rate (2.5 kg a.i. ha −1 ) in a smooth bromegrass–dominated sward; dandelion represented as much as 45% of total biomass in the second harvest of the seeding year.…”
Section: Resultsmentioning
confidence: 99%
“…Weed biomass was concentrated in the first harvest and generally decreased in subsequent harvests (data not presented). Rioux (1994) also reported severe weed infestation when alfalfa sod‐seeding followed broadcast application of glyphosate at high rate (2.5 kg a.i. ha −1 ) in a smooth bromegrass–dominated sward; dandelion represented as much as 45% of total biomass in the second harvest of the seeding year.…”
Section: Resultsmentioning
confidence: 99%
“…In spring wheat in clay soil in northern Alberta, higher densities of T. officinale were found under zero tillage systems than under other systems (Arshad et al 1994). In eastern Canada, density was higher in alfalfa that had been seeded directly into grain stubble, as compared to conventionally-seeded alfalfa (Rioux 1994). In sweet corn, T. officinale emergence was not affected by tillage, probably because of the short time between seed dispersal and germination (Mohler and Calloway 1992).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 90%
“…However, the presence of weeds due to reduced weed management did not result in reduced forage quality (Lemieux et al 1987a). Rioux (1994) also showed that dandelion growth increased and alfalfa growth was reduced with delayed establishment in NT compared with conventional tillage practices. Lemieux et al (1987a) suggested that dicots had more impact than monocots on the yield of timothy (Phleum pratense L.) and timothy-clover mixtures.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the red clover yield advantage with NT compared with other tillage practices in 1994 and the absence of tillage effects in other years would indicate that successful establishment and growth of red clover is possible with all tillage systems under a range of environmental conditions. Other studies also showed that forage legumes can be successfully established and high production levels maintained with reduced tillage intensity and NT (Leroux and Harvey 1980;Allen and Entz 1994;Rioux 1994). Still, improved seeding techniques may be required in conservation tillage systems to reduce the potential risk of poor red clover establishment and productivity under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation